PERBANDINGAN FISIK FORMULA LIPSTIK DENGAN BASIS LEMAK TENGKAWANG (ILLIPE BUTTER) DAN LEMAK COKLAT (COCOA BUTTER) - Husnul Warnida; Yullia Sukawaty; Fazri Wisnu Ardhita (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Illipe butter and cacao butter have alike physical characteristic. Hence, illipe butter is one of CBS (cacao butter substitute) in food industry. The studi aims to compare the physical properties of illipe butter based lipstick with cacao butter based lipstick. Illipe butter in the study is a vegetable fat from the nut of Shorae mecistopteryx, it has a melting point of 29 ° C. The study was conducted at Pharmaceutical Technology Laboratory of Stikes Samarinda. Lipstick bases consist of illipe butter, cacao butter, carnauba wax, beeswax, lanolin and castor oil. Physical evaluation of lipstick includes homogeneity test, pH test, meting point test, hardness test, patch test, and sensory evaluation. The results showed that all lipstick formulas were homogeneous, stable, and no discoloration during 14 days. The average pH of all lipstick formulas is 5.9. Melting point of illipe buteer based lipstick is 58-59 ° C and 59-60° on cocoa butter based lipstick. Illipe butter brown fat base. Hardness level of illipe butter based lipstick is 433-833 grams, while cocoa butter based lipstick has a hardness level more than 1000 grams. Panelists in sensory evaluation preferred illipe butter based lipstick.